2019
DOI: 10.21776/ub.jels.2019.009.03.06
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening by FTIR Spectroscopic Analysis and Antibacterial Activity of Sesbania grandiflora

Abstract: Sesbania grandiflora is a medicinal plant that has been used by many Indonesian people. They have the ability as antibacterial because they contain bioactive compounds that inhibit bacterial growth. Sesbania grandiflora also contains other active compounds such as tannins, saponins, steroids, flavonoids, and terpenoids. This study aims to determine the antibacterial activity of extracts, n-hexane fraction, ethyl acetate fraction and water fraction of Sesbania grandiflora against Edwardsiella tarda using the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The shape of the spectrum was examined, and unique peaks suggesting functional groups possessed by a compound were identified [12]. The absorption bands developed during FTIR identification of S. Grandiflora revealed that the n-hexane fraction contained flavonoids and terpenoids [13]. Investigating in vitro antioxidants and FTIR analysis of Mannar bay seaweed.…”
Section: Introductionmentioning
confidence: 99%
“…The shape of the spectrum was examined, and unique peaks suggesting functional groups possessed by a compound were identified [12]. The absorption bands developed during FTIR identification of S. Grandiflora revealed that the n-hexane fraction contained flavonoids and terpenoids [13]. Investigating in vitro antioxidants and FTIR analysis of Mannar bay seaweed.…”
Section: Introductionmentioning
confidence: 99%